1994
DOI: 10.1111/j.1348-0421.1994.tb01822.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Salmonella Porins as a Broad Spectrum Vaccine Candidate

Abstract: Porins were prepared from smooth strain of Salmonella typhi 0–901 and chemotype of rough mutant of S. typhimurium Ra‐30. Mice were immunized with both the porin preparations in different groups and challenged with S. typhimurium LT2–71 and S. enteritidis SH‐1269. Porin immunized mice showed significant protection (P <0.01) against challenge with homologous as well as heterologous strains. Hence, the use of porins may be attempted in future to protect against salmonellosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 11 publications
1
28
0
Order By: Relevance
“…The increase in DTH response following IROMPs immunization also highlights the importance of cellular factors for the development of protective immunity. Our results are in agreement with reports in which induction of the DTH reaction in response to porin immunization was shown to be responsible for protective immunity in Salmonella infections (Sharma- Rishi et al, 1989;Tabarie et al, 1994;Gupta et al, 1996), where T DTH cells were found to be T cells with surface phenotype of L 3 T 4 / CD4 þ (Mastroeni et al, 1993).…”
Section: Dth Responsesupporting
confidence: 83%
“…The increase in DTH response following IROMPs immunization also highlights the importance of cellular factors for the development of protective immunity. Our results are in agreement with reports in which induction of the DTH reaction in response to porin immunization was shown to be responsible for protective immunity in Salmonella infections (Sharma- Rishi et al, 1989;Tabarie et al, 1994;Gupta et al, 1996), where T DTH cells were found to be T cells with surface phenotype of L 3 T 4 / CD4 þ (Mastroeni et al, 1993).…”
Section: Dth Responsesupporting
confidence: 83%
“…Previous attempts to vaccinate mice against Salmonella using porins, a group of major outer membrane proteins, have demonstrated that these Ags can stimulate a protective response to a challenge strain of limited virulence (13). We have demonstrated here that FliC can provide significant protection to naive C57BL/6 mice and that FliC is also the major target of CD4 ϩ T cells during primary and secondary infection.…”
Section: Discussionmentioning
confidence: 61%
“…However, it is not known which Ags are responsible for inducing such resistance, and there have been few reports of successful immunization of susceptible mice with purified Salmonella proteins. The best characterized of these are the Salmonella porins, which have been shown to protect susceptible mice against challenge with virulent Salmonella (13). A number of other bacterial extracts have been shown to be effective in protecting against Salmonella infection, but the identity of the immunizing Ag was not determined (14,15).…”
mentioning
confidence: 99%
“…Since the mid-1980s, a major OMP of Salmonella has been the subject of much investigation, and our earlier work has shown that porins afford protection against Salmonella infection [6][7][8][9]. Several workers have demonstrated porins to be important antigens, which elicit CMI responses through a delayed-type hypersensitivity reaction, interleukin-2 (IL-2) and interferon-g (IFN-g) production, and mitogenic effects on T and B cells [4,10].…”
Section: Introductionmentioning
confidence: 99%